Analysis of Magnetic Susceptibility in Vertical Sediments in the Fish Pond Area of Limboto Lake - Tang, Bunga; Yunginger, Raghel; Yunus, Muhammad; Patuti, Indriati Martha; Gafur, Nurfitri Abdul; Jahja, Mohamad; Ramadani, Andi Indra Wulan Sari; Meidji, Icha Untari; Supu, Idawati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Limboto Lake is one of the lakes in Indonesia that has been degraded due to sedimentation and waste disposal, which will affect the lake ecosystem and its surroundings. This research aims to analyze the Magnetic Susceptibility in Vertical Sediments in the fish pond area of ​​Limboto Lake. Efforts must be made to trace sediment's contribution, which is controlled by lithogenic and anthropogenic components. Vertical sediment samples from Fish Ponds in Limboto Lake were taken at one point with a depth of 15 meters using an XY-1A Spindle drilling machine. This type of research uses survey techniques and laboratory tests that use rock magnetism methods, especially susceptibility parameter analysis using the Bartington MS2 susceptibility meter instrument at a low frequency of 470 Hz and a high frequency of 4700 Hz to obtain information on the concentration of magnetic minerals. The sediment samples tested did not go through preparation, such as sieving and drying, but the unsifted samples were put into the plastic holder to analyze the susceptibility magnetic parameter. The measurement results show that the low-frequency magnetic susceptibility (XLF) value ranges from 1.11 x 10-8 m3/kg to 9.68 x 10-8 m3/kg. The concentration of magnetic minerals in this sample contains paramagnetic minerals, and based on the XFD % value, which ranges from 0.206% to 4.714% with an average value of 1.170%, the magnetic minerals in the samples tend to be dominated by coarse-grained non-superparamagnetic minerals (>0.03 µm) and tend to occupy stable single-domain (SSD) and multi-domain (MD) domains. Magnetic susceptibility parameters tested using sediment samples without going through a sieving process can be used to determine sediment characteristics in lake areas that tend to be controlled by anthropogenic components.